Ungkapan Istilah ‘Mas-Mas Jawa’ sebagai Representasi Budaya Jawa dalam Media Sosial Tiktok - RR. Balqis Alyamayadita Rahman (Sutasoma : Jurnal Sastra Jawa, 2023)
Abstract The use of linguistic forms which are influenced by the speaker's thoughts can be explained through the meaning process, one of which is the expression of the term "mas-mas Jawa" which requires interpretation of the representation of the term. This research aims to examine the representation of Javanese culture that appears through the term "mas-mas Jawa" on the social media Tiktok. The research method used is qualitative with descriptive analysis techniques. The data collection method is in the form of tapping using a free and skilled listening technique. The data source for this research is TikTok video content which contains the term "mas-mas Jawa." The research results show that a language can show the culture that develops in certain groups of society. Through the term "mas-mas Jawa" which is currently being used virally by Tiktok users, there is a community representation of Javanese culture in an abstract form in the form of life values, a social form in the form of people's personalities, and a physical form in the form of batik as typical clothing. The personality of Javanese men can reflect Javanese culture because in its formation it cannot be separated from cultural influences. From the research conducted, it can be concluded that the representation of TikTok users regarding the term “mas-mas Jawa” is a reflection of the principles of Javanese life, namely sepi ing pamrih, rame ing gawe, memayu hayuning Bawana. Keywords: representation; term; Javanese men; Javanese cultur; tiktok